Perception of time compressed speech in bilinguals - Sheets Vasudevan N (Journal of All India Institute of Speech and Hearing, 1970)
The present investigation reports on the performance of thirty young adults (native and non-native speakers of Hindi with a high level of proficiency inEnglish) on the time compressed version of English and Hindi sentences. The study aimed at- Analysing the influence of time compression (40, 50, and 60 percentcompressin rates) on sentential stimuli in English and Hindi.- Establishing, if any, the differences between the perception of timecompressed speech stimuli in English and Hindi by Speakers proficientin both the languages.- Evaluating the effects of levels of proficiency in a language on the perceptionof time compressed stimuli.